QUALITY CHARACTERIZATION AND ANTIOXIDANT PROPERTIES OF ROSE PERIWINKLE CRUDE DRUGS - Hartanti, Dwi; Charisma, Shintia Lintang; Rinawati, Jeri; Hamad, Alwani (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Leaves and flowers of rose periwinkle (Catharanthus roseus (L.) G. Don) are used for traditional diabetes management in Banyumas, Indonesia. This study evaluated the selected quality characters, total flavonoid content (TFC), total phenolic content (TPC), and the antioxidant activities of rose periwinkle crude drugs. Plant materials were collected from three locations in the Baturraden and Sumbang subdistricts and dried using an artificial heat drying rack to obtain crude drugs. The crude drugs' quality characters, TFC, TPC, and antioxidant activities were evaluated using standard methods. The quality characters of the crude drugs were specified as follows: loss on drying (9.12±0.50%), total ash (8.20±0.71%), acid-insoluble ash (0.24±0.06%), water extractable (28.82±6.77%), and ethanol extractable (35.17±1.79%). The chromatographic profile was generated from chloroform-methanol (8:2) separation over silica GF254. The TFC and TPC were 7.66±0.48 mg Quercetin equivalent (QE)/g and 7.27±1.07 mg Gallic acid equivalent (GAE)/g, respectively. The antioxidant activities were 148.95±12.00 Trolox equivalent (TE)/g for DPPH radical scavenging activity and 651.14±77.91 mM TE/g for FRAP. The DPPH radical scavenging activity and FRAP were weakly to moderately correlated to TPC and TFC. The phenolic compound and flavonoid contents of physicochemically-characterized rose periwinkle were not significantly correlated to their antioxidant activities.